World Vaccine Trials Congress 2012. (August 2012) - Fallon, Jonathan K; Gulley, James L
Gaylord National Convention Center, National Harbor, MD, USA, 11–12 April 2012 The successful design and implementation of vaccine clinical trials is a long and complicated process. Determining trial size, choosing an appropriate end point, managing diverse trial sites, and collecting detailed safety data are just some of the challenges faced along the way. At the World Vaccine Trials Congress 2012, presenters from academia, government agencies, industry and nonprofit organizations described their experiences dealing with these challenges. Also highlighted were newer issues related to the increasing globalization of infectious disease vaccine trials, the clinical development of promising cancer vaccines, and the emergence of electronic data-collection tools. The conference thus provided valuable insights into the present and future of the vaccine trial enterprise.